DOKTRIN “RESPONSIBILITY TO PROTECT” DALAM PENANGANAN KEJAHATAN TERHADAP KEMANUSIAAN DI REPUBLIK SUDAN TAHUN 2023: The Principle Of "Responsibility To Protect" In Addressing Crimes Against Humanity In The Republic Of Sudan In 2023 - Yonathan Andrew; Ayu Nrangwesti (Reformasi Hukum Trisakti, 2024)
Differing views on sovereignty and intervention gave birth to the Responsibility to Protect (R2P) principle which emphasizes the responsibility of states to protect their people from war crimes, crimes against humanity, and ethnic cleansing. The armed conflict in Sudan showed violations of the R2P principle that caused thousands of casualties and sexual violence. The problem of this article is the status of the R2P principle in international law and whether the UN Security Council resolution implementing R2P can be a precedent for applying the R2P principle in Sudan. This article is normative juridical research, descriptive-analytical in nature, using secondary data, qualitative data processing, and deductive conclusions are drawn. The results show that the position of the R2P principle is internationally recognized in various UN documents and resolutions and the UN Security Council has not applied the R2P principle in the case of Sudan.